Simultaneous spectrophotometric determination of copper, nickel, and zinc using 1-(2-thiazolylazo)-2-naphthol in the presence of triton x-100 using chemometric methods - Low, K.H.; Mohd, M.A.; Misran, M.; Md Abas, M.R.; Zain, Sharifuddin Md (2009)
Multivariate models were developed for the simultaneous spectrophotometric determination of copper (II), nickel (II) and zinc (II) in water with 1-(2-thiazolylazo)-2-naphthol as chromogenic reagent in the presence of Triton X-100. To overcome the drawback of spectral interferences, principal component regression (PCR) and partial least square (PLS) multivariate calibration approaches were applied. Performances were validated with several test sets, and their results were then compared. In general, no significant difference in analytical performance between PLS and PCR models. The root mean square error of prediction (RMSEP) using three components for Cu 2+, Ni 2+ and Zn 2+ were 0.018, 0.010, 0.011 ppm, respectively. Figures of merit such as sensitivity, analytical sensitivity, limit of detection (LOD) were also estimated. High reliability was achieved when the proposed procedure was applied to simultaneous determination of Cu 2+, Ni 2+ and Zn 2+ in synthetic mixture and tap water.